1998
DOI: 10.1016/s0896-6273(00)80597-8
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Plasminogen Activator Contributes to the Late Phase of LTP and to Synaptic Growth in the Hippocampal Mossy Fiber Pathway

Abstract: The expression of tissue plasminogen activator (tPA) is increased during activity-dependent forms of synaptic plasticity. We have found that inhibitors of tPA inhibit the late phase of long-term potentiation (L-LTP) induced by either forskolin or tetanic stimulation in the hippocampal mossy fiber and Schaffer collateral pathways. Moreover, application of tPA enhances L-LTP induced by a single tetanus. Exposure of granule cells in culture to forskolin results in secretion of tPA, elongation of mossy fiber axons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
338
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 383 publications
(352 citation statements)
references
References 55 publications
12
338
2
Order By: Relevance
“…Furthermore, both PAR1 (Striggow et al, 2001), and NMDA receptor subunits (Ishii et al, 1993) are highly expressed in brain regions involved with emotional learning, including hippocampus and amygdala. These results it well with suggestions that serine proteases can impact learning (Baranes et al, 1998;Pawlak et al, 2002;Nagai et al, 2004Nagai et al, ,2006Pang et al, 2004;Pawlak et al, 2005), and may suggest that PAR1 is a substrate at which serine proteases such as plasmin exert their actions.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, both PAR1 (Striggow et al, 2001), and NMDA receptor subunits (Ishii et al, 1993) are highly expressed in brain regions involved with emotional learning, including hippocampus and amygdala. These results it well with suggestions that serine proteases can impact learning (Baranes et al, 1998;Pawlak et al, 2002;Nagai et al, 2004Nagai et al, ,2006Pang et al, 2004;Pawlak et al, 2005), and may suggest that PAR1 is a substrate at which serine proteases such as plasmin exert their actions.…”
Section: Discussionsupporting
confidence: 86%
“…We have previously demonstrated a critical role for BDNF within the amygdala in the acquisition of emotional learning in vivo (Rattiner et al, 2004a,b;Chhatwal et al 2006), raising the possibility that protease-mediated activation of BDNF may partially underlie these effects. Studies of LTP suggested that removal of tPA, which converts plasminogen to plasmin, can decrease late phase LTP in hippocampal slices (Baranes et al, 1998). These data are consistent with the idea that serine proteases may regulate synaptic plasticity in the CNS.…”
Section: Introductionsupporting
confidence: 81%
“…Many reports indicate an involvement of the tPA-plasmin system in synaptic plasticity and remodeling (Baranes et al, 1998;Fiumelli et al, 1999;Neuhoff et al, 1999), control of the direction of BDNF's functions (Martinowich et al, 2007), regulation of long-term potentiation (Pang et al, 2004), pathophysiology of mood disorders (Eskandari et al, 2005;Tsai, 2006) and stress-induced anxiety . The neurotrophic effects of lithium in stressinduced hippocampal atrophy and antidepressant effects of this drug in rodent models (Wood et al, 2004;O'Brien et al, 2004) suggest a critical role of BDNF in these lithium-induced actions (reviewed in Chuang, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Smad3/4 has a prominent role in regulating the expression of proteins involved in neuronal survival/death, differentiation, and plasticity (reviewed in Sanyal et al, 2004;Gomes et al, 2005). One of the Smad3/4-regulated protein targets is plasminogen activator inhibitor type-1 (PAI-1, also referred to as Serp1), which binds and inactivates tissue-type plasminogen activator (tPA), a multifaceted protein implicated in neurite outgrowth (Krystosek and Seeds, 1981), neuronal migration (Moonen et al, 1982;Seeds et al, 1999), learning (Qian et al, 1993;Seeds et al, 1995), excitotoxicity (Tsirka et al, 1995), synaptic plasticity (Baranes et al, 1998;Fiumelli et al, 1999;Neuhoff et al, 1999), stress response , and pathogenesis of mood disorders (Eskandari et al, 2005;Tsai, 2006). Using small interfering RNA (siRNA) and dominant negative mutants specific to GSK-3α and GSK-3β, we recently reported that GSK-3α inhibition causes an upregulation of Smad3/4-dependent transactivation and PAI-1 protein levels, while inhibition of GSK-3β induces a downregulation of Smad3/4 transactivation and PAI-1 expression (Liang and Chuang, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that tPA has an important role in synaptic activity (Qian et al, 1993). Indeed, tPA is stored in synaptic terminals, and neuronal tPA is connected to events associated with the development of synaptic plasticity, such as motor learning (Seeds et al, 1995) and long-term potentiation (Baranes et al, 1998).…”
Section: Introductionmentioning
confidence: 99%